Exhausting T Cells During HIV Infection May Improve the Prognosis of Patients with COVID-19 - Lin, Hua-Song; Lin, Xiao-Hong; Wang, Jian-Wen; Wen, Dan-Ning; Xiang, Jie; Fan, Yan-Qing; Li, Hua-Dong; Wu, Jing; Lin, Yi; Lin, Ya-Lan; Sun, Xu-Ri; Chen, Yun-Feng; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
T-cell reduction is an important characteristic of the coronavirus disease 2019 (COVID-19), and its immunopathology are a subject of debate. It may be due to a direct effect of the virus on T cell exhaustion, or indirectly due to T-cell redistributing to lung. HIV/AIDS naturally served as a T cell exhaustion disease model for us to recognize how immune system work in duration of COVID-19. We respectively collected clinical charts, T lymphocyte analysis, and chest CT for HIV patients with laboratory confirmed COVID-19 infection who were admitted to Jin Yin-Tan Hospital (Wuhan, China). Median age of the 21 patients was 47 (IQR 40–50) and median CD4 cell count was 183 cells/μl (IQR 96-289). 11 HIV patients were in non-AIDS stage and 10 were in AIDS stage. Nine patients received antiretroviral treatment (ART) and 12 patients did not receive any treatment. Compared to the reported mortality rate (nearly 4-10%) and severe rate (up to 20-40%) among hospital patients with COVID-19, 21 HIV/AIDS patients showed benign duration with 0% severe and mortality rate. The severity of COVID-19 was similar in non-AIDS patients (median CD4, 287 cells/μl) and AIDS patients (median CD4, 97 cells/μl), even if some AIDS patients have baseline lung injury aroused from HIV: 7 patients (33%) was mild (5 in non-AIDS group and 2 in AIDS group), 14 patients were (67%) moderate (6 in non-AIDS group and 8 in AIDS group). More important, we found that reduction in T-cell numbers positively correlates with serum levels of IL-6 and CRP, which was contrary to the reported findings of immune response in patients with COVID-19 (lower CD4 T cells with higher level of IL-6 and CRP). In HIV/AIDS, a compromised immune system with a lower CD4 counts level might waive clinical symptoms and inflammatory responses, which suggested lymphocyte redistribution as immunopathology lead to lymphopenia in COVID-19.